Impacto de los desastres naturales sobre la educación básica en Colombia (2017)
Natural disasters have increased in frequency and damages in recent decades. The aim of this research is to analyze the impact of disasters caused by climatic phenomena on education in Colombia, particularly on academic performance and dropout of a specific student cohort. For this, difference in differences method with propensity score matching and longitudinal models at school level between 2009 and 2013 are implemented, and emphasis is placed on the role of damages to school physical infrastructure and families. The results show that natural disasters do not affect drop-out rates, however, they do negatively affect school performance through damages to physical infrastructure of schools and damages to housing and crops.